The Method of Taking the Blessing Ball for Manual Robots at the 2018 Indonesian Robot Contest - Septian, Andi; Sapto Aji, Wahyu (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
KRAI (Indonesian Abu Robot Contest) is a robotics contest between Higher Education in Indonesia. Indonesian ash robot contest organized by the Directorate General of Higher Education (DIRJEN DIKTI). The winner of the KRAI will represent Indonesia in the ABU (Asia-Pacific Broadcasting Union) Robocon which is held annually with locations moving around within ABU member countries. KRAI 2018 made a blessing ball picking robot with a gripper. The parameter that must be achieved is that the optimization of the robot drive can take the blessing ball. The design of the blessing ball picking mechanic can use the servo gripper by determining the slope of the robot. The angle of inclination of the robot determines the taking of the ball. Based on the results of the study, the results were obtained by testing carried out taking test data with an angle of 20 ?-50 ?. The robot can pick up when 1 ball with that angle. Testing with an angle of 50 ?-80 ?. The robot can take 2 balls with that angle. Testing with an angle of 80 ?-110 ?. The robot can take 3 balls with that angle. With an angle of 110 ?-140 ?. The robot can take 2 balls. With a blade of 140 ?-170 ? the robot can take 1 ball. In the method of taking the ball in the 10 tests that have been carried out, there are experiments that are declared efficient to be able to take 3 balls with a 100% success percentage in an average time of 21 seconds. So it can be implied that the tester at the ball picking used an angle of 80 ?-110 ? more efficiently than the angle of 20 ?-80 ? and 110 ?-170 ?.